2003
DOI: 10.1161/01.cir.0000081779.88132.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different Bypass Techniques on the Serum Troponin-T Levels in Newborns and Children

Abstract: Background-Cardiac troponin-T is a sensitive marker of myocardial damage. In a prospective study, the effect of 2 different pH strategies during cardiopulmonary bypass on ischemic myocardial injury and clinical outcome was measured in a pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The metric we derived performs as well or better as a predictor of clinical outcome when compared to the IS or other derivations of an inotrope score. Maximum VIS in the first 24 hours has biologic plausibility as a measure of illness severity and predictor of outcome as previously literature demonstrates a nadir in cardiac output after bypass [1], higher risk of cardiac arrest [11], and peaking serum markers of inflammation [12] and myocardial injury [13, 14] during this time period.…”
Section: Discussionmentioning
confidence: 93%
“…The metric we derived performs as well or better as a predictor of clinical outcome when compared to the IS or other derivations of an inotrope score. Maximum VIS in the first 24 hours has biologic plausibility as a measure of illness severity and predictor of outcome as previously literature demonstrates a nadir in cardiac output after bypass [1], higher risk of cardiac arrest [11], and peaking serum markers of inflammation [12] and myocardial injury [13, 14] during this time period.…”
Section: Discussionmentioning
confidence: 93%
“…Some clinical studies have suggested that, in infants, pH-stat provide some neuronal (7,8) and myocardial protection (9) compared to alpha-stat strategy. Other studies (10) have indicated that use of alpha-stat versus pH-stat acid-base management strategy during reparative infant cardiac operations with DHCA-CPB was not consistently related to either improved or impaired early neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A review recommended that the best management of acid–base therapy is dependent upon patient age, with the use of a pH-stat in pediatric patients and an alpha-stat in adult patients [ 180 ]. The results of a clinical trial also confirmed that the pH-stat is superior in the pediatric population [ 181 ].…”
Section: Preventionmentioning
confidence: 80%